Second-order local multiplier algebras of continuous trace C*-algebras - Massey, Pedro Gustavo (2013)
We determine the injective envelope and local multiplier algebra of a continuous trace C*-algebra A that arises from a continuous Hilbert bundle over an arbitrary locally compact Hausdor space. In addition, we show that the second-order local multiplier algebra M_loc^[2](A) of any such algebra A is injective.